2006
DOI: 10.1177/13670069060100020201
|View full text |Cite
|
Sign up to set email alerts
|

Do bilinguals have different concepts? The case of shape and material in Japanese L2 users of English

Abstract: AcknowledgmentsWe are grateful to Yuki Tokumaru and Jean-Marc Dewaele for help at different stages of the experiment. AbstractAn experiment investigated whether Japanese speakers' categorization of objects and substances by shape or material is influenced by acquiring English. Based on Imai and Gentner (1997), subjects were presented with an item such as a cork pyramid and asked to choose between two other items that matched it for shape (plastic pyramid) or for material (piece of cork). The hypotheses were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
95
2
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(105 citation statements)
references
References 24 publications
3
95
2
2
Order By: Relevance
“…In Japanese, many common nouns are treated as mass nouns, and there is a grammatical category, classifier, used to quantify nouns (e.g., "three apples" in English versus "three pieces of apple" in Japanese). Imai and Gentner (1997) and Cook et al (2006) found that this crosslinguistic difference influenced monolingual Japanese and English speakers' preferences for object categorization. Japanese speakers tended to categorize objects as being similar on the basis of their material properties, whereas English speakers tended to categorize objects as being similar on the basis of shape.…”
Section: Prior Studiesmentioning
confidence: 99%
“…In Japanese, many common nouns are treated as mass nouns, and there is a grammatical category, classifier, used to quantify nouns (e.g., "three apples" in English versus "three pieces of apple" in Japanese). Imai and Gentner (1997) and Cook et al (2006) found that this crosslinguistic difference influenced monolingual Japanese and English speakers' preferences for object categorization. Japanese speakers tended to categorize objects as being similar on the basis of their material properties, whereas English speakers tended to categorize objects as being similar on the basis of shape.…”
Section: Prior Studiesmentioning
confidence: 99%
“…Finally, the same multicompetent population used character viewpoint in gesture, where gestures depict events as they were experienced by protagonists, less frequently than monocompetent speakers of Japanese, favoring instead observer viewpoint, where gestures depict events as they were witnessed by the speaker, also employed by monocompetent English speakers (Brown, 2008). In work on other language pairings, Su (2010) Cook et al (2006) found that, after controlling for proficiency, only advanced Japanese users of English resident in England for more than three years categorized objects in a way resembling native English speakers, drawing on similarity of shape as opposed to material. Importantly, however, the studies described above supporting L2 influences on the L1 at an intermediate level employed purely linguistic tasks and made claims about language comprehension and production.…”
Section: Multicompetence and Variation In Native Language Productionmentioning
confidence: 99%
“…Cook et al, 2006;Dussias and Sagarra, 2007;Laufer, 2003; although see Pavlenko & Jarvis, 2002, for lack of effects of length of residence, as well as Bylund, 2009, andGathercole andMoawad, 2010, for effects of age of acquisition).…”
Section: Multicompetence and Variation In Native Language Productionmentioning
confidence: 99%
“…The observed behavior was attributed to the count-mass grammatical conceptualizations in the two languages. In another study, Cook et al (2006) found that while English monolinguals tended to categorize items based on their shape and Japanese monolinguals tended to categorize items based on their substance, Japanese-English bilinguals used both systems for categorizing items, providing further evidence for the claim that learning a language can have an impact on the language learners' cognitive processing beyond language.…”
Section: L2 Language-construal Interfacementioning
confidence: 92%
“…Research has indicated that learning new languages can lead to the acquisition of new categorization systems (Athanasopoulos, 2007;Cook et al, 2006). For instance, it has been shown that speakers of Japanese, a language in which nouns are mass-like, tend to categorize items based on their material or substance, while speakers of English, a language in which number is grammatically marked and count nouns are distinguished from mass nouns, usually prefer to categorize objects based on their shape (Imai and Gentner, 1997).…”
Section: L2 Language-construal Interfacementioning
confidence: 99%